Linking electronic journals - Lessons from the Open Journal project - Hitchcock, Steve; Carr, Les; Hall, Wendy; Harris, Steve; Probets, Steve; Evans, David; Brailsford, David F. (ISSN 1082-9873, 1998)
The Open Journal project has completed its three year period of funding by the UK Electronic Libraries (eLib) programme (Rusbridge 1998). During that time, the number of journals that are available electronically leapt from a few tens to a few thousand. Some of these journals are now developing the sort of features the project has been advocating, in particular the use of links within journals, between different primary journals, with secondary journals data, and to non-journal sources. Assessing the achievements of the project and considering some of the difficulties it faced, we report on the different approaches to linking that the project developed, and summarise the important user responses that indicate what works and what does not. Looking ahead, there are signs of change, not just to simple linking within journals but to schemes in which links are the basis of "distributed" journals, where information may be shared and documents built from different sources. The significance has yet to be appreciated, but this would be a major change from printed journals. If projects such as this and others have provided the initial impetus, the motivation for distributed journals comes, perhaps surprisingly, from within certain parts of the industry, as the paper shows.